The Implementation of Ttw With Mic Approach and Verbal Feedback Via Lms Toward the Mathematics Representation Based on Metacognition - Kusumaningtyas, Argi Ayu Sulistyani; Kartono, Kartono; Noor Asih, Tri Sri (Universitas Negeri Semarang, 2021)
Learning with a teacher-centered model had not been able to optimize students’ higher-order thinking ability. It made the students’ metacognition were not maximum especially dealing with the mathematical representation ability. This research aimed to describe the mathematics representation ability based on the metacognitive categories. This research applied a combination method of sequential explanatory with regression test for the quantitative data. The results showed the metacognition influenced mathematics representation ability. Students with reflective use categories could identify and analyze the questions properly. They could also evaluate the answers although some of them did not write the questions into correct mathematics sentences. Students with strategic use categories could identify and analyze the questions properly but they did not evaluate their answers. Students with aware use could identify but they were a lack in analyzing and evaluating. Then, students with the tacit use category were not found. Teachers should direct the students with more development and counseling in a personal manner to overcome the gaps.